Sliki iz kroga Giandomenica in Lorenza Tiepola iz nekdanje zbirke Ludvika viteza Gutmannsthala-Benvenutija - Meke, Katra (Annales. Series historia et sociologia, 2015)
The article presents the fate of two tiepolesco paintings once in the collection of Ludvik knight Gutmannsthal- Benvenuti in Novi dvor by Radeče. The latter represents one of the many cases of mass noble inventory sales taking place in the first half of the 20th century. The formation of the collection was probably most intense in the time of the acquisition of the Novi dvor by Radeče (1860) for its interior equipment with purchases in Italy, Germany etc. After Ludvik's death in 1890 the collection was inherited by his wife Marija and after her death only a year later the owner became their son Nikolaj knight Gutmannsthal-Benvenuti. In 1926 he started to sell the estate Novi dvor with its inventory due to his move to Rome to assume the office of the chamberlain of Pope Pius XI. Otherwise, France Stele was trying to keep the collection in the broader Yugoslavian area, but there was no interest on behalf of cultural institutions, mostly due to financial difficulties. Consequently, an export permission for 95 paintings was issued. Stele carefully documented the collection with photographs and written documentation, which facilitates the identification and allows us to trace works appearing in the art market or becoming part of other gallery collections. The data mentioned above made it possible, with the help of the internet, to identify both paintings and to reveal their fate.
Keywords: 19.st.; 19th cent.; 20.st.; 20th cent.; art market; beneško slikarstvo; collecting; collection sales; Glava filozofa s turbanom; Gutmannsthal-Benvenuti, Ludvik, 1810-1890; Head of a Turbaned Philosopher; Marija z otrokom in liščkom; Novi dvor by Radeče; Novi dvor pri Radečah; prodaja zbirk; Settecento; The Madonna and Child with a Goldfinch; Tiepolo, Giambattista, 1696-1770; Tiepolo, Giandomenico, 1727-1804; Tiepolo, Lorenzo, 1736-1776; umetnostni trg; Venetian painting; zbiranje